2006
DOI: 10.1089/acm.2006.12.1003
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use Among Asian-American Subgroups: Prevalence, Predictors, and Lack of Relationship to Acculturation and Access to Conventional Health Care

Abstract: CAM use varies across Asian-American subgroups. Acculturation and access to conventional medical care is unrelated to any CAM use for most Asian-American subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
4
54
1
Order By: Relevance
“…Asian American elderly-the majority of whom are foreign-born immigrants-appear to use emotional self-care to counteract depressive experiences, and are less likely to seek professional medical help or take prescription medicine then are native-born American elderly (Hsiao et al, 2006). Specific self-care strategies for Asian mental health include cognitive, religious, physical, social and artistic approaches of coping (Pang, 1996;Sue, 2005).…”
Section: Asian American Mental Health and Resiliencymentioning
confidence: 99%
“…Asian American elderly-the majority of whom are foreign-born immigrants-appear to use emotional self-care to counteract depressive experiences, and are less likely to seek professional medical help or take prescription medicine then are native-born American elderly (Hsiao et al, 2006). Specific self-care strategies for Asian mental health include cognitive, religious, physical, social and artistic approaches of coping (Pang, 1996;Sue, 2005).…”
Section: Asian American Mental Health and Resiliencymentioning
confidence: 99%
“…A study showed that non-Latino whites and Japanese Americans who were more religious were less likely to use overall CAM, whereas increased spirituality was associated with higher overall CAM use. 24 However, this study was unable to examine the role of religiosity and spirituality with non-R/S CAM use in the cancer population.…”
mentioning
confidence: 94%
“…1,28,31,42 Unfortunately, small sample sizes of Asian subgroups precluded more detailed examination of variation by country of origin. 43,44 The effects of the remaining predisposing factors were in the expected directions, similar to those for general CAM use and for acupuncture. 1,10,17,30,33,45 A limitation of the NHIS is that it does not include information on health and illness beliefs and values, predisposing factors known to be associated with CAM use.…”
mentioning
confidence: 56%